KI 2018 : advances in artificial intelligence : 41st German Conference on AI, Berlin, Germany, September 24-28, 2018, Proceedings /: advances in artificial intelligence : 41st German Conference on AI, Berlin, Germany, September 24-28, 2018, Proceedings. (2018) - Unknown
No abstract available